Combing the Hairy Ball Using a Vector Field Without Equilibria - Carvalho, Tiago; Gonçalves, Luiz Fernando [UNESP] (Springer Nature, 2019)
The main goal of this paper is to present a piecewise smooth vector field tangent to S2 without equilibrium points. Moreover, we will show that this vector field contains a chaotic non-trivial minimal set.
Keywords: Chaos; Minimal set; Piecewise smooth vector field